Degradation diagnostics for Li4Ti5O12-based lithium ion capacitors: insights from a physics-based model - Madabattula,G; Wu,B; Marinescu,M; Offer,G (Journal of The Electrochemical Society, 2020)
Lithium ion capacitors are an important energy storage technology, providing the optimum combination of power, energy and cycle life for high power applications. However, there has been minimal work on understanding how they degrade and how this should influence their design. In this work, a 1D electrochemical model of a lithium ion capacitor with activated carbon (AC) as the positive electrode and lithium titanium oxide (LTO) as the negative electrode is used to simulate the consequences of different degradation mechanisms in order to explore how the capacity ratio of the two electrodes affects degradation. The model is used to identify and differentiate capacity loss due to loss of active material (LAM) in the lithiated and de-lithiated state and loss of lithium inventory (LLI). The model shows that, with lower capacity ratios (AC/LTO), LAM in the de-lithiated state cannot be identified as the excess LTO in the cell balances the capacity loss. Cells with balanced electrode capacity ratios are therefore necessary to differentiate LAM in lithiated and de-lithiated states and LLI from each other. We also propose in situ diagnostic techniques which will be useful to optimize a LIC's design. The model, built in COMSOL, is available online.